PARAMETERS AFFECTING QUALITATIVE AND EFFICIENT ELECTRODEPOSITION OF METALS IN AN ELECTROLYTIC CELL: A REVIEW (FUDMA JOURNAL OF SCIENCES, 2020)
Electroplating has been a useful practice in the laboratory and industry for a long time. Its usefulness is more profound in oil industries for corrosion prevention and control, automobile industry, jewelries and decoration. Today, the scope of electroplating has expanded considerably with many players exploring its advantages and optimizing its parameters for enhanced productivity. The paper presented a review of electroplating with the aim of making concise information available on its process parameters and its process optimization. The review was compiled from several major work which pertained to parameters affecting qualitative and efficient electrodeposition of metals in an electrolytic cell. Results gathered included actual effect of identified parameters and interplay of parameter on quality of electrodeposition and microstructure of deposited metal. Important recommendations were made to further enhance the practice of electrodeposition.
Keywords: Electroplating, Efficient Electrodeposition, Electrodes, Electrolyte, Operating Parameters